All kinds of courage; stories about boys and girls of yesterday and today. - Gruenberg, Sidonie Matsner, 1881-1974; Lewicki, James (Garden City, N.Y., Doubleday, 1962)
Thirty-nine short stories by such authors as Armstrong Sperry, Elizabeth Coatsworth, Cornelia Meigs, Eric Kelly, Pearl Buck, and Elizabeth Yates, describing the courage to give up a beloved possession, to defend a classmate before taunting peers, or to admit a wrong without making excuses.
Keywords: Children's stories; Short stories